Effectiveness of Visual Cueing Versus Dual Task Exercise on Improving Walking Ability in Early-Stage Parkinson's Subjects. - Lilly, N. Sharon; Chakravarthi, Ch. Ashok; Durga Chinni, K. Divya; Raghunadh, N.; Sitaramachaaryulu, P. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Parkinson's disease is a neurological condition that worsens over time. Parkinson's disease primarily affects dopaminergic neurons in the substantia nigra of the midbrain. Parkinson's disease is commonly associated with walking difficulties such as postural instability and a shuffling gait. Physiotherapy interventions such as Tai Chi, strength training, body weight support treadmill training, visual cueing, and dual task training are few of the techniques that are frequently used for gait training and to enhance balance. Most often employed strategies for improving walking ability are dual tasking and visual cueing. Many studies showed the advantages of visual cueing and dual-task training for enhancing gait in Parkinson's disease, but there are no research studies done to directly evaluate the efficacy of these two therapeutic modalities alongside standard physiotherapy in individuals with early-stage Parkinson's disease. This study compares the impact of dual-task workouts and visual cueing on enhancing walking abilities in individuals with early-stage Parkinson's disease. Methods: A quasi experimental study design, out of 64 subjects, sixty subjects who satisfied the inclusion criteria were split into two groups: thirty in Group A (visual cueing) and thirty in Group B (dual tasking) with mean age of 50-65 years. Interventions were administered in both groups, five days in a week for six weeks. Outcome measures were analyzedusing ink footprint analysis, gait parameters such as step length, stride length, velocity, and cadence were observed. Result: The results were analyzed using paired T-test to measure pre and post test results within group. When comparing between groups, the analysis of variance (ANOVA) showed a substantial improvement in group B (dual tasking) when compared toGroup A (visual cueing) p<0.01. Conclusion: The findings of this study suggest that walking ability significantly improved after 6 weeks of dual task training and visual cueing exercises along with traditional physiotherapy. However, when compared between groups, it was found that dual tasking exercises is more effective in improving walking ability than visual cueing exercises.